Review of Milko Kelemen: Olifant, Milko Kelemen: Abecedarium, Gerhard Holzer: Concerto, Joseph Schwantner: Consortium, and Krzystof Meyer: Concerto da Camera - Casken, John (Contact: A Journal for Contemporary Music (1971-1990), 1976)
-